Magnesium intake and insulin resistance in obese adolescent girls - Harry Freitag Luglio Muhammad; Emy Huriyati; Rina Susilowati; Madarina Julia (Indonesian Pediatric Society, 2009)
Background The worldwide increase in the prevalence ofcardiovascular diseases in adulthood is related to obesity inchildren and adolescents. Insulin resistance and hyperinsulinemia observed in obese individuals are the precursors of cardiovascular diseases and type 2 diabetes mellitus. Magnesium, through its action on insulin receptors, is proposed to be an important factor in preventing insulin resistance.Objective The aim of this study was to assess the associationbetween magnesium intake and insulin resistance in obeseadolescent girls.Methods This was a cross-sectional study on obese adolescentgirls in Yogyakarta, Indonesia. Insulin resistance was defined as a HOMA-IR index of3.16 or more. HOMA-IR was calculated usingfasting insulin and plasma glucose levels. Magnesium intake andenergy adjusted magnesium intake were measured using a 24-hour food recall method on 6 non-consecutive days.Results Of 7 8 obese adolescent girls included in our study, 56% of them were found to be insulin resistant. Magnesium intake was only 61 o/o of the recommended daily requirement for adolescent girls. There were no significant associations between magnesium intake and either HOMA-IR or hyperinsulinemia.Conclusion Our study does not find an association betweeninsulin resistance and magnesium intake in obese adolescent girls.